2013
DOI: 10.1177/0885066613482086
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Intraperitoneal Catheters in Neonates Following Open Heart Surgery

Abstract: The PPC insertion can be easily performed at the bedside with minimal complications. Fluid balance management is facilitated, and ventilation is improved. The PPC insertion is a valuable addition to the armamentarium of the physician treating neonates in the intensive care unit after complex congenital heart surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…57 In some reports, mortality in children undergoing cardiac surgery has been reduced if dialysis is commenced before significant fluid overload occurs. 33,58,59 Peritoneal dialysis is safe in infants and children after cardiac surgery 57,[59][60][61][62][63][64][65] and may also be useful in the prevention of fluid overload in high-risk patients. A case-matched cohort study comparing patients with a PD catheter placed at the time of surgery to others of similar age and surgical complexity demonstrated that these patients were less likely to develop fluid overload, had shorter durations of mechanical ventilation, had shorter ICU stays, and did not have an increase in expenditures.…”
Section: Management Of Aki and Fluid Overloadmentioning
confidence: 99%
“…57 In some reports, mortality in children undergoing cardiac surgery has been reduced if dialysis is commenced before significant fluid overload occurs. 33,58,59 Peritoneal dialysis is safe in infants and children after cardiac surgery 57,[59][60][61][62][63][64][65] and may also be useful in the prevention of fluid overload in high-risk patients. A case-matched cohort study comparing patients with a PD catheter placed at the time of surgery to others of similar age and surgical complexity demonstrated that these patients were less likely to develop fluid overload, had shorter durations of mechanical ventilation, had shorter ICU stays, and did not have an increase in expenditures.…”
Section: Management Of Aki and Fluid Overloadmentioning
confidence: 99%
“…4 As advocates of peritoneal drains would submit, this randomized trial by Ryerson and colleagues 1 does not refute the fact that in selected patients passive peritoneal drainage may effectively treat intra-abdominal hypertension and thereby mitigate the progression toward progressive kidney injury. 3,5,6 Moreover, tacit in this analysis is the fact that, for pediatric patients who experience acute kidney injury in the setting of congenital heart surgery, perioperative mortality ranges as high as 28% to 67%, and initiation of adjuncts such as PD in the first days after surgery may considerably decrease this risk. 3,7 Finally, no single-center study can reliably account for intraoperative practice variations (eg, size of the bypass circuit or use of modified ultrafiltration) that could influence the overall postoperative utility of such adjunctive therapies at other centers.…”
Section: Jonathan M Chen Mdmentioning
confidence: 99%
“…This study was not powered to detect differences in these outcomes, and we further speculate that a somewhat larger study focused on complete AVSD would show statistically significant improvements. Though not routine, placement of peritoneal catheters is not uncommon [4][5][6][7][8][9] and thus, a multicenter trial is feasible.…”
Section: Commentsmentioning
confidence: 99%
“…In some centers, peritoneal drainage catheters are used as adjuncts to traditional methods of mitigating postoperative fluid overload in this patient population [4][5][6][7][8][9]. These catheters are typically placed intraoperatively and are allowed to drain passively to gravity, acting as an additional means of removing unwanted extravascular fluid.…”
Section: Introductionmentioning
confidence: 99%